2022
DOI: 10.3390/biology11101410
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomes and Their Role in Regulating the Metabolism of Hematopoietic Stem Cells

Abstract: Hematopoietic stem cells (HSCs) have the capacity to renew blood cells at all stages of life and are largely quiescent at a steady state. It is essential to understand the processes that govern quiescence in HSCs to enhance bone marrow transplantation. It is hypothesized that in their quiescent state, HSCs primarily use glycolysis for energy production rather than mitochondrial oxidative phosphorylation (OXPHOS). In addition, the HSC switch from quiescence to activation occurs along a continuous developmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 193 publications
0
5
0
Order By: Relevance
“…This protective mechanism affects HSC quiescence and function by limiting cytokine receptor signaling and autophagy [54]. The high number of lysosomes and their activity are critical in order to complete mitochondrial clearance in HSCs and to preserve their quiescent characteristics [55,56].…”
Section: Hematopoietic Stem Cells (Hscs)mentioning
confidence: 99%
“…This protective mechanism affects HSC quiescence and function by limiting cytokine receptor signaling and autophagy [54]. The high number of lysosomes and their activity are critical in order to complete mitochondrial clearance in HSCs and to preserve their quiescent characteristics [55,56].…”
Section: Hematopoietic Stem Cells (Hscs)mentioning
confidence: 99%
“…To better understand the mechanisms by which lysosomes affect cancer development, A GSVA analysis was performed using the de ned gene sets (KEGG and Hallmark), and glycolysis, mTOR targets, DNA repair, and myc-targets were identi ed as lysosome-related pathways in cluster 2. Previous studies showed that lysosomal activity may play a role in preserving the quiescence of hematopoietic stem cells by modifying glycolysis-mitochondrial biogenesis 23 . In addition, the mTOR targets, DNA repair, and myctargets are all involved in the autophagic process and are essential for lysosome formation and transformation [24][25][26] .…”
Section: Discussionmentioning
confidence: 99%
“…To better understand the mechanisms by which lysosomes affect cancer development, A GSVA analysis was performed using the defined gene sets (KEGG and Hallmark), and glycolysis, mTOR targets, DNA repair, and myc-targets were identified as lysosome-related pathways in cluster 2. Previous studies showed that lysosomal activity may play a role in preserving the quiescence of hematopoietic stem cells by modifying glycolysis-mitochondrial biogenesis [ 33 ]. In addition, the mTOR targets, DNA repair, and myc-targets are all involved in the autophagic process and are essential for lysosome formation and transformation [ 34 36 ].…”
Section: Discussionmentioning
confidence: 99%